Municipal wastewater treatment using constructed wetland and limestone - Neny Soffiana, Sofyan Effendy (2010)
In the present investigation, I report on the results of a system using tanks filled with limestone rocks followed by vegetative tank (water hyacinth) to treat sewerage treatment plant (STP) located at Kampung Melayu, Gambang. Removal of heavy metals, ammonia nitrogen, TSS, BOD 5, COD, turbidity from municipal wastewater has been studied. Based on the results, it shows pH, BOD 5 , Cu, Zn, Fe and Pb tested comply with Standard B in Environmental Quality Act, 1979 but COD, Mn and Total Suspended Solid (TSS) were greater than Standard B. It was indicated that the concentrations of five heavy metals (Zn, Cu, Pb, Fe, Mn) in the wastewater were rather low. After the treatment with limestone and water hyacinth, all these stated parameters comply with Standard B with overall percentage removal were ranged from 30.43 %, to 99.39 %. The result demonstrates that limestone was more effective in contaminant removal in STP but if it was combined together it is such a good combination. i [Jhilik organic pollutants, met al do not undergo •4egadation arid generally need to be removed through highly expensive clean-up methods. The effectiveness of heavy metals removal from municipal wastewater was high, except for manganese with removal of 6718%.The other metals undergo removals ranged from 7.25% to 99.39 %. The most effective parameter treated was zinc with the fastest optimum contact time which is 3 days with 87.44% for limestone and 94.22 for water hyacinth tank. Analysis of effectiveness of metals removal during wastewater treatment processes undoubtedly indicates the fundamental role of limestone and constructed wetland with vegetative (water hyacinth) in metals removal.